IMPROVEMENT OF PATIENT SAFETY IN DIABETIC ULCER PATIENT: HOLISTIC APPROACH THROUGH INNOVATION IN WOUND CARE AND FALL PREVENTION - Zaharany, Tsania Ayu; Putri, Gusrina Komara; Saudi, La; Sari, Nina Imelda (Jurnal Pengabdian Masyarakat Dalam Kesehatan, 2025)
Introduction: Fall is a common problem that happens in diabetic patients, and because of it, it becomes a health concern for them. Health issues in diabetic ulcer patients are low quality of life, decreased activity, social isolation, decreased productivity, and depression due to frequent falls. This community service aims to organize several events to improve awareness of safety for patients with diabetic ulcers. Methods: The community service was conducted within two months, starting from May 1st to May 26th 2023, in Community Health services with a total of eleven respondents. Activities begin with planning, obtaining permits, monitoring, analyzing data, providing interventions and implementation, followed by evaluation. In this activity, three teaching staff members were involved who were lecturers in the field of nursing, and one student. Results: The community service action found that there was a difference between the pre- and post-intervention scores. It shows that the level of knowledge in risk of fall is generally at a good level p p-value = 0,043 (p < 0,05. Besides that, after nursing intervention, there was improvement in stability of blood glucose (The deviation pre- post post-intervention of blood glucose level is 17%.) and improvement of wound healing without inflammation and pus. Conclusion: This intervention could improve cognitive, affective, and skills of diabetic ulcer patients and improve community empowerment.